Mathematical modelling of biosensors with substrate and product degeneration - Stonkienė, Liana; Ivanauskas, Feliksas (Lietuvos matematikos rinkinys, 2012)
This paper presents a one-dimensional-in-space mathematical model of the amperometric biosensors with substrate and product degeneration. The model is based on diffusion equations containing a non-linear term related to Michaelis-Menten kinetics of the enzymatic reactions. It was analyzed effect of substrate and product degeneration for the biosensors response.